Prognostic impact of tumor size reduction assessed by magnetic resonance imaging after radiochemotherapy in patients with locally advanced cervical cancer - Cordoba, Abel; Durand, Benedicte; Escande, Alexandre; Taieb, Sophie; Amor, Mariem Ben Haj; Le Deley, Marie Cecile; Michel, Andree; Le Tinier, Florence; Hudry, Delphine; Martinez, Carlos; Leblanc, Eric; Becourt, Stephanie; et al. (Frontiers in Oncology, 2022)
Objective: Pelvic magnetic resonance imaging (MRI) is a key exam used for the initial assessment of loco-regional involvement of cervical cancer. In patients with locally advanced cervical cancer, MRI is used to evaluate the early response to radiochemotherapy before image-guided brachytherapy, the prognostic impact of which we aimed to study. Methods: Patients with locally advanced cervical cancer treated using concomitant radiochemotherapy followed by closure treatment between January 2020 and December 2015 were included in this study. Clinical, anatomopathological, radiological, therapeutic, and follow-up data were evaluated. Results: 232 were included for evaluation (median follow-up period, 5.3 years). The median age was 50 years (range, 25–83 years), and the median tumor size was 47.5 mm (range, 0–105 mm). Based on the International Federation of Gynaecology and Obstetrics classification system, 9 patients were in stage IB2; 20, IB3; 2, IIA; 63, IIB; 4, IIIA; 7, IIIB; and 127, IIIC1 or higher. The re-evaluation MRI was performed at the median dose of 55.5 Gy, and median reduction in tumor size was 55.2% (range, −20–100%). There was a difference between the disease-free and overall survival rates of the patients with a tumor response greater or lesser than 50%. The risk of recurrence or death reduced by 39% in patients with a tumor size reduction >50%. The overall 5-year survival rate of patients with a response greater and lesser than 50% were 77.7% and 61.5%, respectively. The 5-year disease-free survival rate for these two groups of patients were 68.8% and 51.5%, respectively. Conclusion: Our study confirms the prognostic impact of tumor size reduction in terms of disease-free and overall survival rates that was evaluated using MRI data obtained after radiochemotherapy in patients with locally advanced cervical cancer.